Polyphenol (−)-Epigallocatechin Gallate (EGCG) mitigated kidney injury by regulating metabolic homeostasis and mitochondrial dynamics involvement with Drp1-mediated mitochondrial fission in mice - Chu, Yue-Lei; Pi, Jin-Chan; Yao, Yu-Fei; Chen, Xuan-Ying; Peng, Xiao-Ping; Li, Wen-Juan (Food and chemical toxicology, 2024)
The study aimed to examine effects of (−)-epigallocatechin-3-gallate (EGCG) on energy metabolism and mitochondrial dynamics in mouse model of renal injury caused by doxorubicin (DOX). Here, mice were divided into Control group, EGCG-only treated group, DOX group, and three doses of EGCG plus DOX groups. Our results showed that EGCG behaved beneficial effects against kidney injury via attenuation of pathological changes in kidney tissue, which was confirmed by reducing serum creatinine (SCr), blood urea nitrogen (BUN), and apoptosis. Subsequently, changes in reactive oxygen species generation, malondialdehyde content, and activities of antioxidant enzymes were considerably ameliorated in EGCG + DOX groups when compared to DOX group. Furthermore, EGCG-evoked renal protection was associated with increases of mitochondrial membrane potential and decreases of mitochondrial fission protein Dynamin-related protein 1 (Drp1). Moreover, changing glycolysis into mitochondrial oxidative phosphorylation was observed, evidenced by controlling activities of malate dehydrogenase (MDH) and hexokinase (HK) in EGCG + DOX groups when compared to DOX group, indicating that reprogramming energy metabolism was linked to EGCG-induced renal protection in mice. Therefore, EGCG was demonstrated to have a protective effect against kidney injury by reducing oxidative damage, metabolic disorders, and mitochondrial dysfunction, suggesting that EGCG has potential as a feasible strategy to prevent kidney injury. [Display omitted] •EGCG mitigated doxorubicin (DOX)-induced kidney injury by attenuating apoptosis.•Renal protection of EGCG via modification of redox system and mitochondrial disorder.•EGCG-mediated mitochondrial protection via mitigating abnormal energy metabolism.•Reducing Drp1-evoked mitochondrial fission was implicated in renal protection of EGCG.